Scale dependency of conservation outcomes in a forest-offsetting scheme - Giannichi, Marta Lisli (Conservation biology : the journal of the Society for Conservation Biology, 2020)
© 2019 The Authors. Conservation Biology published by Wiley Periodicals, Inc. on behalf of Society for Conservation Biology.